Students' Problems in Speaking Activities - Putri, Adela Dwi; Abdullah, Umar; Amalia, Hariana (Jadila: Journal of Development and Innovation in Language and Literature Education, 2025)
The purpose of this study was to find out students' problems in speaking English activities. This study used a qualitative method with a case study research design to find out the students’ problems speaking at SMAN 1 Sungai Keruh. Data were collected through interviews with four students and one English teacher, Selected with through convenience case strategy. The data were analyzed thematically. This study found seven problems experienced by students in speaking, including (1) psychology problems such as a lack of confidence, shyness, and anxiety; (2) lack of motivation due to a lack of practice, indifference and no motivation to learn English; (3) fear of making mistakes such as reluctant to speak for fear of making mistakes in pronunciation and grammar, afraid to speak because they had traumatic experiences; (4) participation challenges which were low or uneven participation in class and limited interaction; (5) the use of mother tongue; (6) inhibition that referred to experiencing limited vocabulary, lack of time for speaking practice, difficulties in composing sentences and grammar, feeling as though they had nothing to say; and (7) peer negative and social influence.